Roles of lncRNAs in pancreatic beta cell identity and diabetes susceptibility - Pullen, Timothy J.; Rutter, Guy A. (Frontiers in Genetics, 2014)
Type 2 Diabetes usually ensues from the inability of pancreatic beta cells to compensate for incipient insulin resistance. The loss of beta cell mass, function and potentially beta cell identity contribute to this dysfunction to extents which are debated. In recent years, long non-coding RNAs (lncRNAs) have emerged as potentially providing a novel level of gene regulation implicating critical cellular processes such as pluripotency and differentiation. With over 1000 lncRNAs now identified in beta cells, there is growing evidence for their involvement in the above processes in these cells. While functional evidence on individual islet lncRNAs is still scarce, we discuss the how lncRNAs contribute to Type 2 Diabetes susceptibility, particularly at loci identified through Genome Wide Association Studies (GWAS) as affecting disease risk.